Letters and Musical Sketches. Toward a Proper Integration of Bellini’s Writings. - Laura Mazzagufo; Pietro Sichera; Daria Spampinato; Angelo Mario Del Grosso (Journal of the Text Encoding Initiative)
This article examines the use of XML-based technologies to encode verbal and musical texts in two publishing products featuring autograph material by Vincenzo Bellini (1801–1835), held at the Museo civico Belliniano in Catania, Italy. The first product is a digital scholarly edition (DSE) of Bellini’s autograph letters, encoded using the XML-TEI vocabulary. The second project involves the encoding of Bellini’s musical sketches, which often complement the letters by providing concrete examples of his compositional techniques. An experimental approach using the Music Encoding Initiative (MEI) vocabulary was adopted for these sketches: this encoding process required custom solutions to address the texts’ unique features, such as authorial interventions, the sketches’ embryonic nature, the copresence of musical notation and textual annotations, and the interrelations of different studies. This article therefore examines formal representational strategies and challenges encountered during the encoding process, particularly for musical texts, and presents an initial proposal aimed at properly integrating information from the TEI-encoded verbal texts and MEI-encoded musical texts, using an approach modeled after the Web Annotation Data Model (WADM) and its current implementation in TEI. We believe that the integration of these practices, technologies, and data is a means to unravel Bellini’s compositional process and his artistic sensibility, thereby enhancing both scholarly research and public engagement with his work.